PENDAMPINGAN PENENTUAN HARGA POKOK PRODUKSI BAGI PELAKU UMKM DI DESA SAMPALAN KLOD KLUNGKUNG - Putu Pande R. Aprilyani Dewi; Ni Putu Budiadnyani; I G A Desy Arlita; Putu Putri Prawitasari (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2024)
Micro, Small and Medium Enterprises (MSMEs) have an important function in developing an economy in Indonesia. MSMEs are considered as businesses that are able to survive in the midst of an economic crisis, the proof is that the government entrusts MSMEs to reduce the negative impacts of the economic crisis, where like the Covid-19 pandemic that is currently sweeping the world, Indonesian people choose to become MSMEs as a choice for business. One of the problems faced by MSME actors is that there are still difficulties in determining the cost of production (HPP). Most business actors in Sampalan Klod Village, Klungkung, are still blind to the importance of bookkeeping and lack understanding in calculating the cost of production. The implementation of this activity consists of 2 main activities, namely presenting material related to the importance of determining the cost of production because it is to find out how much costs are incurred in processing raw materials into finished goods that are ready to be sold as well as providing education on how to determine the cost of production and helping the public in calculating and create cost of production. With this training, several MSME business actors have succeeded in determining the cost of goods produced and knowing the profit earned each month.